2013
DOI: 10.2147/idr.s46002
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic sensitivity pattern of uropathogens from pregnant women with urinary tract infection in Abakaliki, Nigeria

Abstract: BackgroundUrinary tract infection (UTI) is a common bacterial infection during pregnancy and a significant cause of perinatal and maternal morbidity and mortality. The causative bacteria have remained virtually the same although with variations in individual prevalence. There has been an increasing resistance by these bacteria to the commonly available antibiotics.ObjectivesTo determine the prevalence of UTI, the common causative bacteria, and their antibiotic sensitivity pattern among pregnant women with UTI.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
57
8
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(89 citation statements)
references
References 14 publications
19
57
8
5
Order By: Relevance
“…This is in conformity with different studies elsewhere in the world which indicated that most UTIs are caused by bacteria mainly gram negatives that live in the bowel [1, 2]. Moreover, other studies in Ethiopia, Nigeria and India have demonstrated similar findings [35, 14]. This study also showed that E.coli , K. pneumonia , P. aureginosa and S. aureus accounted for 77.6% of the isolates.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in conformity with different studies elsewhere in the world which indicated that most UTIs are caused by bacteria mainly gram negatives that live in the bowel [1, 2]. Moreover, other studies in Ethiopia, Nigeria and India have demonstrated similar findings [35, 14]. This study also showed that E.coli , K. pneumonia , P. aureginosa and S. aureus accounted for 77.6% of the isolates.…”
Section: Discussionsupporting
confidence: 91%
“…This trend conforms to findings of other studies done in Ethiopia [3, 5] and overseas in India [4]. In contrast, a study in Nigeria [14] has reported that the most common isolated organisms from urine culture were E. coli followed by S. aureus . Possible explanation for this difference in isolation rate might be related to variation in geographical location and time which is also stated by other studies in the country and abroad [5, 7].…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence in this study was close to 13.2% found in Mangalore, Karnataka in India [21]. Higher prevalence (46.6%, 46.5%) for ASB was found in Bangalor in India, Abakaliki Nigeria and lower prevalence of 12.8% in Abuja [22][23][24]. Therefore ASB prevalence differs from setting to setting.…”
Section: Discussionsupporting
confidence: 67%
“…Therefore ASB prevalence differs from setting to setting. E. coli is the most common isolate in ASB as it was also confirmed in a prospective study in Odisha state, India and in Abuja (56.%) [19][20][21][22][23]. CoNS is one of isolated uropathogens [25].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation